THE VALUE OF MISOPROSTOL IN PATIENTS USING NSAIDs - Levent DEMİRTÜRK; Saadeddin HÜLAGÜ; İlhan KARABEKİR; Sabahattin GÜL; Zeki ÇANKIR; Mehmet ALTIN; Metin ERTÜRK (Turkish Journal of Gastroenterology, 2020)
-